ANALISIS SISTEM TATA KELOLA KEUANGAN PEMBANGUNAN DESA (STUDI KASUS DESA GROGOL KECAMATAN TULANGAN KABUPATEN SIDOARJO) - Rokhilah, Khilmiatur; Zaman, Komarun; Darim, Abu (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
Grogol Village, Tulangan District, is one of the districts in Sidoarjo that has received a Village Fund budget of Rp. 1 billion more than the 2021 State Budget (APBN). Grogol Village, Tulangan District, is in Sidoarjo Regency, East Java, Indonesia. Village funds are used for village development and can solve poverty problems in rural areas. This research was conducted with the aim of finding out how the financial management of village development funds is managed in Grogol Village, Tulangan District, Sidoarjo Regency and to find out how the positive impact of village development funds is in Grogol Village, Tulangan District, Regency Sidoarjo. This research uses descriptive qualitative method, data sources used are premier and secondary data. The techniques used in data collection are observation, interviews, and documentation. In the steps of analyzing the data, namely collecting data, summarizing data, presenting data, drawing conclusions. The results showed that the financial management of village development funds in Grogol Village, Tulangan District, Sidoarjo Regency in the process of managing village funds there are three stages, namely the planning stage, the implementation stage, and the reporting and accountability stages have been quite effective where the funds budgeted for village development in Grogol Village have been properly realized so as to have a positive impact on the people of Grogol Village in the form of increasing the welfare of the community as a whole.